Fast IP handoff support for VoIP and multimedia applications in 802.11 WLANs - Christos Bouras; Ioanna Sampraku; T Karoubalis (IEEE International Symposium on a World of Wireless, Mobile and Multimedia Networks - WoWMoM 2005, Taormina, Italy, 2005)
Wireless LANs (WLANs) have edged into numerous mobile and wireless users’ daily experience worldwide as a mainstream connectivity solution for a broad range of applications. Even though WLANs offer very high channel bandwidth, they show long network-layer handoff latency. This is a restraining factor for mobile clients using interactive multimedia applications such as voice over IP (VoIP) or video streaming. This paper presents an 802.11-dependent fast IP handoff method which quickly restores IP connectivity for mobile clients running next generation WLAN applications such as Voice over WLANs (VoWLAN). This method outperforms other existing proposed IP mobility solutions in 802.11 WLANs as verified from real performance testing, while introduces insignificant compulsory additions to the existing 802.11 wireless LAN framework.